Linguistic nativism and the poverty of the stimulus - Clark, Alexander (Alexander Simon); Lappin, Shalom; Wiley InterScience (Online service) (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2011)
This unique contribution to the ongoing discussion of language acquisition considers the Argument from the Poverty of the Stimulus in language learning in the context of the wider debate over cognitive, computational, and linguistic issues.: Critically examines the Argument from the Poverty of the Stimulus - the theory that the linguistic input which children receive is insufficient to explain the rich and rapid development of their knowledge of their first language(s) through general learning mechanisms Focuses on formal learnability properties of the class of natural languages, considered.
Front Matter -- Introduction: Nativism in Linguistic Theory -- Clarifying the Argument from the Poverty of the Stimulus -- The Stimulus: Determining the Nature of Primary Linguistic Data -- Learning in the Limit: The Gold Paradigm -- Probabilistic Learning Theory for Language Acquisition -- A Formal Model of Indirect Negative Evidence -- Computational Complexity and Efficient Learning -- Positive Results in Efficient Learning -- Grammar Induction through Implemented Machine Learning -- Parameters in Linguistic Theory and Probabilistic Language Models -- A Brief Look at Some Biological and Psychological Evidence -- Conclusion -- References -- Author Index -- Subject Index.
Includes bibliographical references and index.
Print version record.
Keywords: Language acquisition; Native language; Computational linguistics; Language and languages; Computational linguistics; Language acquisition; Native language; Electronic books